Juridical Analysis Of The Use Of The Company's Shares As An Object Of Fiduciary Guarantee - Natasya Ferena; Erniyanti Erniyanti; Markus Gunawan; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze juridically the use of the company's shares as an object of fiduciary guarantee in Batam City. The background of this research is rooted in the need for a deep understanding of the effectiveness and security of the company's shares used as fiduciary guarantees, as well as their influence on legal certainty and local economic stability. In Indonesia, the use of shares as fiduciary guarantees is regulated by Law Number 42 of 1999 concerning Fiduciary Guarantees and Law Number 40 of 2007 concerning Limited Liability Companies, but the implementation of this law in the field often encounters various obstacles, especially in Batam City which is a strategic business center. This study uses a qualitative method with a document study approach, in- depth interviews, and field observations to collect data. The subject of this study involves notaries, fiduciary guarantee registration officials, investors, and business actors in Batam. The results of the study show that there are several significant obstacles in the implementation of the use of shares as an object of fiduciary guarantee, which include procedural complexity, variations in notary practices, and limited administrative infrastructure. Despite this, stocks are still a trusted and used instrument because of their liquidity and economic value. Based on these findings, suggestions include expanding education and training for notaries to improve understanding and thoroughness in the fiduciary guarantee administration process. The Batam City Government is advised to update and simplify related regulations to support efficiency and legal certainty. In addition, investments in information technology are needed to modernize the registration and document handling processes, which can increase the transparency and speed of the fiduciary assurance process.